Publication outcomes of the abstracts presented at the 2011 European Congress on Osteoporosis, Osteoarthritis and Musculo-Skeletal Diseases (ECCEO-IOF11). Issue 1 (December 2015) - Rabenda, Véronique; Bruyère, Olivier; Cooper, Cyrus; Rizzoli, René; Buckinx, Fanny; Quabron, Adrien; Reginster, Jean-Yves
Abstract Summary The publication outcomes of the abstracts presented during the ECCEO-IOF 2011 reflect a high research productivity, support the robustness of the selection process conducted by the Scientific Advisory Committee and suggest that IOF-ESCEO WCO is successful in its mission to promote and disseminate research. Background and Objective The European (now World) Congress on Osteoporosis, Osteoarthritis and Musculo-Skeletal Diseases (IOF-ESCEO WCO, formerly ECCEO-IOF) is the largest worldwide event fully dedicated to the clinical, epidemiological, translational and economic aspects of bone, joint and muscle diseases. The role of the Scientific Advisory Committee is to select abstracts for oral communication or poster presentation based on a short summary of the research. The aim of the present survey was to determine the publication rate in international peer reviewed journals of abstracts accepted at the IOF-ESCEO WCO 2011 Meeting (formerly ECCEO-IOF11), the relationship, if any, between the presentation format of the abstract and its subsequent full publication and the impact factor of the journal in which research was published. Results Of 619 abstracts accepted at the 2011 ECCEO-IOF11 annual meeting, 45 were accepted for oral communication and 574 accepted for poster presentation. In the subsequent 3 years (2011–2014), 191 abstracts were published as a full-length manuscript (30.9 %). The publication rate was significantly higher for oral communications (75.6 %) than for poster presentations (27.4 %;p < 0.0001). Publications derived from oral communications were published in journals with a higher impact factor (8.3 ± 10.1) than those arising from poster presentations (4.0 ± 2.3;p < 0.0001), but there was no difference in the time to publication (OC 16.3 [IQR 8.4–23.3] months vs PP 11.3 [IQR 5.3–21.4];p = 0.14). Conclusion These results indicate a high research productivity and an appropriate selection of oral communication by the Scientific Advisory Committee of ESCEO-IOF.